The Kraft Pulp And Paper Properties of Sweet Sorghum Bagasse (Sorghum bicolor L Moench) - Fatriasari, Widya; Supriyanto, Supriyanto; Iswanto, Apri Heri (ITB Journal Publisher, LPPM ITB, 2015)
This study investigated the potency of sweet sorghum (Sorghum bicolor) bagasse as raw material for pulp and paper using kraft pulping. The effects of alkali and sulfidity loading on kraft pulp and paper properties were also investigated. The pulping condition of the kraft pulp consisted of three levels of alkali loading (17, 19 and 22%) and sulfidity loading (20, 22 and 24%). The maximum cooking temperature was 170Â°C for 4 h with a liquid to wood ratio of 10:1. Kraft pulping of this Numbu bagasse produced good pulp indicated by high screen yield and delignification selectivity with a low Kappa number (< 10). The unbleached pulp sheet produced a superior brightness level and a high burst index. The increase of active alkali loading tended to produce a negative effect on the pulp yield, Kappa number and paper sheet properties. Therefore, it is suggested to use a lower active alkaline concentration.